2013
DOI: 10.1111/jnc.12442
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term nicotine treatment down‐regulates α6β2* nicotinic receptor expression and function in nucleus accumbens

Abstract: Long-term nicotine exposure induces alterations in dopamine transmission in nucleus accumbens (NAcc) that sustain the reinforcing effects of smoking. One approach to understand the adaptive changes that arise involves measurement of endogenous dopamine release using voltammetry. We therefore treated rats for 2-3 months with nicotine and examined alterations in nAChR subtype expression and electrically-evoked dopamine release in rat NAcc shell, a region key in addiction. Long-term nicotine treatment selectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 58 publications
5
15
0
Order By: Relevance
“…However, the NAc core, but not the NAc shell, was blocked by a-conotoxins, suggesting that nicotine's effects are mediated by a6*-nAChRs. Although it was previously determined that cholinergic interneurons excite presynaptic nAChRs on DA terminals (Jones et al, 2001;Yang et al, 2009b;Zhang et al, 2009;Brown et al, 2012), we demonstrate here that short-term nicotine administration causes a decrease in evoked DA release in the NAc, as reported previously by others (Zhang et al, 2009;Perez et al, 2013). Under the previous model, direct activation of the nAChR on the DA terminal would induce increased DA release, as a cationic influx into the presynaptic terminal would induce a higher magnitude of vesicular release.…”
Section: Discussionsupporting
confidence: 84%
“…However, the NAc core, but not the NAc shell, was blocked by a-conotoxins, suggesting that nicotine's effects are mediated by a6*-nAChRs. Although it was previously determined that cholinergic interneurons excite presynaptic nAChRs on DA terminals (Jones et al, 2001;Yang et al, 2009b;Zhang et al, 2009;Brown et al, 2012), we demonstrate here that short-term nicotine administration causes a decrease in evoked DA release in the NAc, as reported previously by others (Zhang et al, 2009;Perez et al, 2013). Under the previous model, direct activation of the nAChR on the DA terminal would induce increased DA release, as a cationic influx into the presynaptic terminal would induce a higher magnitude of vesicular release.…”
Section: Discussionsupporting
confidence: 84%
“…Chronic nicotine treatment in vivo led to upregulation (Nguyen et al, 2003;Parker et al, 2004;Visanji et al, 2006;Perez et al, 2008;Henderson et al, 2014), or downregulation of a6*-containing AChRs in rodents and a non-human primate (Lai et al, 2005;McCallum et al, 2006b;Perry et al, 2007;Doura et al, 2008;Perez et al, 2008Perez et al, , 2012Perez et al, , 2013Marks et al, 2014). In mouse brain, a6b2b3* AChRs are three-fold more sensitive to nicotine down-regulation than a4b2* AChRs are to nicotine up-regulation .…”
Section: Neuropharmacology Of A6* Achrs In Dopaminergic Neuronsmentioning
confidence: 97%
“…Interestingly, administration of nicotine results in similar changes in the α4β2* and α6β2* nAChRs levels, and to a similar magnitude as that obtained in the present study with sucrose (Renda and Nashmi, 2014, Exley et al, 2013, Perez et al, 2013. Although the mechanisms responsible for this are still not fully understood, it has been suggested that changes in α4β2* and α6β2* nAChRs contribute to nicotine re-enforcement and self-administration (Madsen et al, 2014, Picciotto and Kenny, 2013, Leslie et al, 2013, De Biasi and Dani, 2011.…”
Section: Discussionsupporting
confidence: 86%